Wybrane organizacyjne aspekty wdrażania i funkcjonowania systemu budżetowania w przedsiębiorstwie - Kotapski, Roman (Budgeting in a company - chosen organizing problems of implementation, 2006)
This article describes problems concerning implementation of budgeting systems in a company. What does a conception of budgeting include? How one can implement budgeting systems in a company? Last part of this article describes organizing problems in budgeting systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 73-80